Pengaruh Strategi Call To Action Marketing dalam Konten Tiktok dan Instagram Terhadap Keputusan Pembelian Pelanggan di Kalangan Mahasiswa Politeknik Negeri Bandung - Muhammad Fadhil Maulana (International Journal Administration, Business & Organization, 2024)
The aim of this research is to determine the extent of the influence of the call to action marketing strategy in TikTok and Instagram content is on customer purchasing decision among Politeknik Negeri Bandung students. A total of 101 respondents, consisting of Politkeknik Negeri Bandung students with various study programs. Data processing in this research utilize descriptive analysis, correlation analysis, and simple linear regression. This research results stated that the call to action marketing strategy in TikTok and Instagram content had a low influence on customer purchasing decision, which had 25,2%, while the remaining 74,8% was influences by other variables beyond the ones investigated.